Comparative Study of Psidium guajava and Ocimum gratissimum Leaf Oils on Adult Maize Weevil (Sitophilus zeamais M.) - Abdulmalik, B.S.; Abdullahi, N. (UMYU Journal of Microbiology Research)
A laboratory study was conducted to determine the efficacy of Psidium guajava and Ocimum gratissimum leaves oil for Sitophilus zeamais control. The experimental design was a completely randomized design with three replications. The leaf oil was extracted using soxhlet extractor. The leaves oil at four levels of concentration was mixed with 20 g of disinfested maize in 2 by 5 cm container. All the treatments with the leaves oil showed significant level of toxicity to the weevil. The highest concentration (4%) of the leaves oil of the plant material tested induced the highest mortality in the S. zeamais after 6days. Grains treated with the leaves oil extract significantly reduced the number of progeny emerged of both FI and F2 respectively by S. zeamais, and evoked low weight loss and seed damage against the weevil on grains treated with the highest dosage of the leaves oil extract. P. guajava was found to be most effective recoding 100% mortality of S. zeamais after 5days,lower LC50 value(1.94µml/l), lower F1 and F2 emergence (0.000±0.000), lower %weight loss (1.00%), lower %seed damage(11%) and higher viability(50%) which compared favourably with that recorded in positive control. Further studies should be conducted to find out the most bioactive ingredient of those plant leave oils.